2017
DOI: 10.1007/s11948-017-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Causal Factors of Corruption in Construction Project Management: An Overview

Abstract: The development of efficient and strategic anti-corruption measures can be better achieved if a deeper understanding and identification of the causes of corruption are established. Over the past years, many studies have been devoted to the research of corruption in construction management (CM). This has resulted in a significant increase in the body of knowledge on the subject matter, including the causative factors triggering these corrupt practices. However, an apropos systematic assessment of both past and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 68 publications
1
107
0
3
Order By: Relevance
“…Web of Science is a powerful, highly recognized academic search engines used by researchers worldwide to track the latest research progress in various areas [34][35][36][37][38]. Thus, this paper selected to use Web of Science to track down those published journal articles relating to sustainable construction project financing.…”
Section: Methodsmentioning
confidence: 99%
“…Web of Science is a powerful, highly recognized academic search engines used by researchers worldwide to track the latest research progress in various areas [34][35][36][37][38]. Thus, this paper selected to use Web of Science to track down those published journal articles relating to sustainable construction project financing.…”
Section: Methodsmentioning
confidence: 99%
“…The literature review carried out in preparing this article revealed that crime in the AEC-industry typically has been examined according to specific perspectives, notably corruption research (Locatelli et al, 2017;Owusu et al, 2017), research on workplace related crime (CIOB, 2009;Golden and Skibniewski, 2010;Zhang et al, 2014;Zitkiene et al, 2016), so-called social dumping (Bengtsson, 2014;Bernaciak, 2016;Fromentin, 2016) and tax evasion schemes (Barth et al, 2008;Behling and Harvey, 2015). A notable exception to this is the momentous work of Williams et al (Williams, 2005;2008;2009a;b;Williams and Nadin, 2012;Williams and Horodnic, 2015), who through a long series of publications have scrutinized what can be called grey zones, that is, patterns of action where criminal and legal activities intertwine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, contrasting to other topical areas (including forms, causes, and anti-corruption measures) that are more generic in corruption-related studies, procurement irregularities are context-specific (Owusu et al, 2017;Le et al, 2014a). Simply put, the variables captured under this construct vary from institution to institution and from country to country.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, studies have been conducted to identify some of the rationales behind corruption and their associated forms other than one's greed for money, especially in the context of construction procurement. Owusu, Chan, and Shan (2017) presented a conceptual framework in a recent review study on the causal factors of corruption in construction projects. The framework encapsulated 44 causal variables captured under five constructs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation